2013
DOI: 10.2147/ndt.s47287
|View full text |Cite
|
Sign up to set email alerts
|

Executive dysfunction in children affected by obstructive sleep apnea syndrome: an observational study

Abstract: IntroductionThe role of sleep in cognitive processes can be considered clear and well established. Different reports have disclosed the association between sleep and cognition in adults and in children, as well as the impact of disturbed sleep on various aspects of neuropsychological functioning and behavior in children and adolescents. Behavioral and cognitive dysfunctions can also be considered as related to alterations in the executive functions (EF) system. In particular, the EF concept refers to self-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 65 publications
2
46
0
1
Order By: Relevance
“…Short sleep duration, insomnia, as well as interrupted sleep due to sleep apnea, nocturnal enuresis, and periodic limb movement in children and adolescents adversely affects learning, academic performance,1723 emotional processing,2426 and – relatedly – psychological functioning 2730. In a cross-sectional survey with a large population of college students (n=1,125; 17–24 years old), over 60% of respondents were categorized as poor-quality sleepers with shorter sleep duration 19.…”
Section: Introductionmentioning
confidence: 99%
“…Short sleep duration, insomnia, as well as interrupted sleep due to sleep apnea, nocturnal enuresis, and periodic limb movement in children and adolescents adversely affects learning, academic performance,1723 emotional processing,2426 and – relatedly – psychological functioning 2730. In a cross-sectional survey with a large population of college students (n=1,125; 17–24 years old), over 60% of respondents were categorized as poor-quality sleepers with shorter sleep duration 19.…”
Section: Introductionmentioning
confidence: 99%
“…The subjects in both groups were recruited from the same urban area; participants were all Caucasian, and held a middle-class socioeconomic status (between class 2 or class 3, corresponding to €28,000–€55,000/year to €55,000–€75,000/year, respectively, according to the current Italian economic legislation parameters), as previously reported 17,45…”
Section: Methodsmentioning
confidence: 99%
“…Further, some studies have suggested a potential causative role of craniofacial morphology in childhood sleep disorders,21 which are usually linked to learning2224 and behavioral impairment 25…”
Section: Introductionmentioning
confidence: 99%